ANALYSIS OF COSTUMER PERCEPTION ABOUT IMPLEMENTATION OF ISO 9001 : 2000 AT PKU MUHAMMADIYAH HOSPITAL, BANTUL - Cahyani Hijriafitri; Marchaban Marchaban; Sumarni Sumarni (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
ISO 9001:2000 is a standard quality management system that focus on processes and customers, since Februari2008 ISO 9001:2000 have been applied in RSU PKU Muhammadiyah Bantul. The aims of this study are to analyzethe increasing level of internal customer satisfaction before and after ISO 9001:2000 and also to measure the patient’ssatisfaction level to find out whether the patients feel satisfied with the service given by inpatient installation afterapplying ISO 9001:2000. The study was done by using analytic cross-sectional method. Data were collected using total sampling method as many as 377 internal customer for internal customer satisfaction questionnaire, while questionnaire of patient’ssatisfaction level used purposive sampling method as many as 69 respondent. As the result, there was an increasing of internal customer satisfaction proved by the difference of averagebetween before implementing ISO as much as 52,48 and about 72,68 after implementing ISO. There is also showedthat found gap between service quality with patient satisfaction and the sequence of gap is responsiveness that isfollowed reliability, empathy, assurance, and tangibles dimension. Keyword : ISO 9001:2000, internal customer satisfaction, importance - performance analysis, ServQual